Whole genome analysis of cephalosporin-resistant Escherichia coli from bloodstream infections in Australia, New Zealand and Singapore: high prevalence of CMY-2 producers and ST131 carrying blaCTX-M-15 and blaCTX-M-27. (14th December 2017) - Harris, Patrick N A; Ben Zakour, Nouri L; Roberts, Leah W; Wailan, Alexander M; Zowawi, Hosam M; Tambyah, Paul A; Lye, David C; Jureen, Roland; Lee, Tau H; Yin, Mo; Izharuddin, Ezlyn; Looke, David; et al.
Abstract: Objectives: To characterize MDR Escherichia coli from bloodstream infections (BSIs) in Australia, New Zealand and Singapore. Methods: We collected third-generation cephalosporin-resistant (3GC-R) E. coli from blood cultures in patients enrolled in a randomized controlled trial from February 2014 to August 2015. WGS was used to characterize antibiotic resistance genes, MLST, plasmids and phylogenetic relationships. Antibiotic susceptibility was determined using disc diffusion and Etest. Results: A total of 70 3GC-R E. coli were included, of which the majority were ST131 (61.4%). BSI was most frequently from a urinary source (69.6%), community associated (62.9%) and in older patients (median age 71 years). The median Pitt score was 1 and ICU admission was infrequent (3.1%). ST131 possessed more acquired resistance genes than non-ST131 ( P  =   0.003). Clade C1/C2 ST131 predominated (30.2% and 53.5% of ST131, respectively) and these were all ciprofloxacin resistant. All clade A ST131 ( n  =   6) were community associated. The predominant ESBL types were bla CTX-M (80.0%) and were strongly associated with ST131 (95% carried bla CTX-M ), with the majority bla CTX-M-15 . Clade C1 was associated with bla CTX-M-14 and bla CTX-M-27, whereas bla CTX-M-15 predominated in clade C2. Plasmid-mediated AmpC genes (mainly bla CMY-2 ) were frequent (17.1%) but were more common in non-ST131 ( P  <   0.001) isolates from Singapore and Brisbane. Two strains carried both bla CMY-2 and bla CTX-M . The majority of plasmid replicon types were IncF. Conclusions: In a prospective collection of 3GC-R E. coli causing BSI, community-associated Clade C1/C2 ST131 predominate in association with bla CTX-M ESBLs, although a significant proportion of non-ST131 strains carried bla CMY-2 .